Mechanisms of enhancer-promoter communication and chromosomal architecture in mammals and Drosophila - Kyrchanova, Olga V.; Bylino, Oleg V.; Georgiev, Pavel G. (Frontiers in Genetics, 2022)
The spatial organization of chromosomes is involved in regulating the majority of intranuclear processes in higher eukaryotes, including gene expression. Drosophila was used as a model to discover many transcription factors whose homologs play a key role in regulation of gene expression in mammals. According to modern views, a cohesin complex mostly determines the architecture of mammalian chromosomes by forming chromatin loops on anchors created by the CTCF DNA-binding architectural protein. The role of the cohesin complex in chromosome architecture is poorly understood in Drosophila, and CTCF is merely one of many Drosophila architectural proteins with a proven potential to organize specific long-range interactions between regulatory elements in the genome. The review compares the mechanisms responsible for long-range interactions and chromosome architecture between mammals and Drosophila.